2011
DOI: 10.1084/jem.20102131
|View full text |Cite
|
Sign up to set email alerts
|

Thymic stromal lymphopoietin fosters human breast tumor growth by promoting type 2 inflammation

Abstract: TSLP released from human breast cancer cells promotes OX40L expression on DCs, and these OX40L-expressing DCs drive development of inflammatory Th2 cells which promote breast tumor development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
202
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(228 citation statements)
references
References 62 publications
(90 reference statements)
13
202
4
1
Order By: Relevance
“…Importantly, residual tumors from CTX-treated patients also contained reduced percentages of B cells and CD4 + T cells. Tumor-infiltrating CD4 + T cells in BC are known to express the T H 2 cytokines IL-4 and IL-13 concomitantly with the production of IFN-γ (25,26), consistent with coexpression of CXCR3 and CCR4 (38, 39) as we observed herein. It remains to be determined whether cytokine production by CD4 + T cells is altered by neoadjuvant CTX; however, the combined reduction in both CD4 + T cells and B cells is indicative of a favorable shift away from a T H 2 microenvironment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Importantly, residual tumors from CTX-treated patients also contained reduced percentages of B cells and CD4 + T cells. Tumor-infiltrating CD4 + T cells in BC are known to express the T H 2 cytokines IL-4 and IL-13 concomitantly with the production of IFN-γ (25,26), consistent with coexpression of CXCR3 and CCR4 (38, 39) as we observed herein. It remains to be determined whether cytokine production by CD4 + T cells is altered by neoadjuvant CTX; however, the combined reduction in both CD4 + T cells and B cells is indicative of a favorable shift away from a T H 2 microenvironment.…”
Section: Discussionsupporting
confidence: 88%
“…CD4 + T cells isolated from human BC produce high levels of type II helper (T H 2) cytokines including IL-4 and IL-13 (25,26), which are significant in light of studies demonstrating that several protumor activities of TAMs are regulated by IL-4 derived from CD4 + T cells (1,27). Based on these findings, we recently reported that infiltration by CD68 + , CD4 + , and CD8 + immune cells in human BC is predictive of overall survival, and that the ratio of CD68 to CD8a mRNA in tumor tissue correlates with complete pathologic response (pCR) in patients undergoing neoadjuvant chemotherapy (CTX) for early stage BC (6).…”
mentioning
confidence: 99%
“…The IL-4-induced decreased antimicrobial peptide secretion by keratinocytes would be one of the potential mechanisms responsible for this increased susceptibility (49). Finally, it has also been recently described that, in a breast cancer, thymic stromal lymphopoietin produced by epithelial cancer cells can induce the development of Th2 cells that promote tumor growth (50). Thus, our results suggest that Th2-derived IL-4 could also impact on the function of pre-existing memory CD8 T cells and contribute to the pleiotropic regulation of the immune response associated with Th2-inducing pathologies.…”
Section: Discussionmentioning
confidence: 98%
“…However, immune regulation in the liver and tumor environment may contribute to tumor outgrowth and limit the efficacy of immunotherapeutic strategies. 10,11 In support of this we and others have described the presence of regulatory CD4 C Foxp3 C T cells in liver tumors, that suppress local antitumor immunity and that are associated with poor patient prognosis. [12][13][14][15][16] Liver TiTreg are characterized by high expression of glucocorticoidinduced tumor necrosis factor receptor related gene (GITR), CTLA-4 and inducible T cell co-stimulator (ICOS).…”
Section: Introductionmentioning
confidence: 57%